Working with youth who have experienced commercial sexual exploitation: voices from the field - Helpingstine, Claire (Violence and victims, 2024)
Little is known about the experiences of service providers working with youth who have experienced commercial sexual exploitation (CSE). In this qualitative study, 12 service providers shared their experiences working with youth who have experienced CSE. Thematic analysis was used to develop key themes that included the challenges posed by working with this population, including the breadth of necessary services and the type of support that is needed for this work. Participants shared the importance of being prepared to work with this population and learn from those with lived experience. The complexity of cases and the difficulty engaging youth who had experienced CSE were also themes. These results can inform service providers who work with youth about the common challenges in working with this population and prepare the next generation of service providers for this difficult work. Training service providers, managing their expectations, and getting them ready for their role will be critical for successful intervention with youth who have experienced CSE.